Endospores associated with deep seabed geofluid features in the eastern Gulf of Mexico. Issue 6 (22nd August 2022) - Rattray, Jayne E.; Chakraborty, Anirban; Elizondo, Gretta; Ellefson, Emily; Bernard, Bernie; Brooks, James; Hubert, Casey R. J.
Abstract: Recent studies have reported up to 1.9 × 10 29 bacterial endospores in the upper kilometre of deep subseafloor marine sediments, however, little is understood about their origin and dispersal. In cold ocean environments, the presence of thermospores (endospores produced by thermophilic bacteria) suggests that distribution is governed by passive migration from warm anoxic sources possibly facilitated by geofluid flow, such as advective hydrocarbon seepage sourced from petroleum deposits deeper in the subsurface. This study assesses this hypothesis by measuring endospore abundance and distribution across 60 sites in Eastern Gulf of Mexico (EGM) sediments using a combination of the endospore biomarker 2, 6‐pyridine dicarboxylic acid or 'dipicolinic acid' (DPA), sequencing 16S rRNA genes of thermospores germinated in 50°C sediment incubations, petroleum geochemistry in the sediments and acoustic seabed data from sub‐bottom profiling. High endospore abundance is associated with geologically active conduit features (mud volcanoes, pockmarks, escarpments and fault systems), consistent with subsurface fluid flow dispersing endospores from deep warm sources up into the cold ocean. Thermospores identified at conduit sites were most closely related to bacteria associated with the deep biosphere habitats including hydrocarbon systems. The high endospore abundance at geological seep features demonstrated here suggests that recalcitrant endospores and their chemical components (such as DPA) can be used in concert with geochemical and geophysical analyses to locate discharging seafloor features. This multiproxy approach can be used to better understand patterns of advective fluid flow in regions with complex geology like the EGM basin.